Microbial alteration in marine sediments: Insights from compound-specific isotopic compositions of amino acids in subseafloor environments - Choi, Hyuntae; Choi, Bohyung; Chikaraishi, Yoshito; Takano, Yoshinori; Kim, Haryun; Lee, Kitack; Lim, Dhongil; Shin, Kyung-Hoon (Frontiers in Marine Science, 2022)
The proportion of amino acids (AAs) in sediment can be used as an indicator of microbial degradation, which is primarily the product of benthic prokaryote activity. The microbial activity would be reflected with the stable isotope ratio of nitrogen (δ15N) at the time of mineralization and resynthesis of AAs. In this study, the compound-specific isotope analysis of individual AAs was used to investigate δ15N variation associated with microbial processes in marine sediment samples. Our results showed a decrease in AA concentrations in core-top sediment was accompanied by an increase in δ15N values, suggesting large 15N enrichment in buried AAs. Phenylalanine displayed an increase in δ15N from the surface to depths greater than 2 cm, whereas relatively constant δ15N values at depths below 2 cm, suggesting that microbial utilization of phenylalanine varies with depth. Glycine showed the highest relative molar contribution (from 12.1 to 36.4%), with the largest δ15N increase (from 0.8 to 8.7) in deep sediment, implying that such information can serve as a measure of AA diagenesis in sedimentary environments. Our results also indicated that the δ15N values of individual AAs in sediment reflected the microbial alteration of organic matter at water-sediment interfaces and in sub-surface environments. These findings form an important basis for interpreting the δ15N values of AAs in sediment.